Stability study of ZnO nanoparticles in aqueous solutions of carboxylate anions; Journal of Nanoparticle Research; Vol. 17 - Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Karepina E. E. Elizaveta Evgenjevna; Yunda E. N. Elena Nikolaevna; Lyamina G. V. Galina Vladimirovna; Kosova N. I. Nataljya Ivanovna; Kuznetsov D. V. Denis Valerjevich (2015, 2015)
Title screen